(untitled) (Temas de Nuestra América Revista de Estudios Latinoaméricanos, 2022)
Thinking is always an action that commits to transformation, this is the thread by which Latin American thought has been raising awareness, the need to establish a utopian thought that achieves this goal. That is why it is necessary to outline some ideas around what this category implies from the contributions made by the academic Horacio Cerutti Guldberg, thus allowing it to be assumed as part of the baggage of Latin American thought. Proposing alternatives to the fragmented and dehumanized realities with which we live on a daily basis.